2020
DOI: 10.1097/jcn.0000000000000667
|View full text |Cite
|
Sign up to set email alerts
|

Stroke Survivors' Feelings and Perceptions of Their Recovery After a Tai Chi Exercise Intervention

Abstract: Background Most tai chi studies conducted among stroke survivors have focused on physical functioning, whereas inclusion of stroke survivors' feelings and perceptions of participating in tai chi is lacking. Objective The aim of this study was to identify stroke survivors' feelings and perceptions of participating in a tai chi intervention during their poststroke recovery. Methods This qualitative descriptive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 26 publications
4
3
0
1
Order By: Relevance
“…In addition, they were surprised and pleased about how their ability to do the tai chi movements improved each week. Our findings that these stroke survivors experienced greater personal efficacy beliefs after participating in tai chi is similar to findings from a prior qualitative study with participants reporting greater confidence in their body and their own abilities [ 20 ]. Moreover, a mixed methods study examining the feasibility of tai chi for stroke rehabilitation [ 14 ] reported significantly greater self-efficacy in performing activities of daily living post-intervention.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…In addition, they were surprised and pleased about how their ability to do the tai chi movements improved each week. Our findings that these stroke survivors experienced greater personal efficacy beliefs after participating in tai chi is similar to findings from a prior qualitative study with participants reporting greater confidence in their body and their own abilities [ 20 ]. Moreover, a mixed methods study examining the feasibility of tai chi for stroke rehabilitation [ 14 ] reported significantly greater self-efficacy in performing activities of daily living post-intervention.…”
Section: Discussionsupporting
confidence: 87%
“…However, natural freer breathing was mentioned frequently in the tai chi classes [ 11 , 39 ]. Moreover, we found that the social interactions and sense of belonging among these stroke survivors was a key active ingredient with therapeutic value as in prior studies [ 14 , 20 , 21 ], which led to self-discovery [ 11 , 13 , 40 ]. Furthermore, participants related a collective sense of the shared experience during the focus group, which was illuminated during the focus group interactions.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Tai Chi is a safe form of exercise for stroke survivors, including those with hemiparesis or poststroke depression [ 36 , 37 , 56 ], though intervention safety or adverse events are frequently not reported [ 57 59 ]. While stroke survivors typically report great enjoyment and satisfaction when performing Tai Chi [ 37 , 56 , 60 ], the acceptability or fidelity of Tai Chi interventions among stroke survivors are frequently not reported [ 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%